2015
DOI: 10.1039/c5ee01076d
|View full text |Cite
|
Sign up to set email alerts
|

Functional integration of Ni–Mo electrocatalysts with Si microwire array photocathodes to simultaneously achieve high fill factors and light-limited photocurrent densities for solar-driven hydrogen evolution

Abstract: An n + p-Si microwire array coupled with a two-layer catalyst film consisting of Ni-Mo nanopowder and TiO 2 light-scattering nanoparticles has been used to simultaneously achieve high fill factors and lightlimited photocurrent densities from photocathodes that produce H 2 (g) directly from sunlight and water.The TiO 2 layer scattered light back into the Si microwire array, while optically obscuring the underlying Ni-Mo catalyst film. In turn, the Ni-Mo film had a mass loading sufficient to produce high catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 28 publications
(74 reference statements)
2
61
0
Order By: Relevance
“…High FF values in Si microwire photocathodes have been obtained by covering the bottom area between the microwires with Ni-Mo/TiO 2 (ref. 2 ) or cobalt phosphide nanoparticles 2,3 . The bestperforming Si homojunction microwire array photocathodes from these studies demonstrated an ideal regenerative cell efficiency, η irc , of 2.9 and 2.8% respectively [2][3][4] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High FF values in Si microwire photocathodes have been obtained by covering the bottom area between the microwires with Ni-Mo/TiO 2 (ref. 2 ) or cobalt phosphide nanoparticles 2,3 . The bestperforming Si homojunction microwire array photocathodes from these studies demonstrated an ideal regenerative cell efficiency, η irc , of 2.9 and 2.8% respectively [2][3][4] .…”
mentioning
confidence: 99%
“…2 ) or cobalt phosphide nanoparticles 2,3 . The bestperforming Si homojunction microwire array photocathodes from these studies demonstrated an ideal regenerative cell efficiency, η irc , of 2.9 and 2.8% respectively [2][3][4] . These efficiencies, obtained in designs without surface passivation, were restricted by light absorption, evidenced by a limited photocurrent (< 15 mA cm −2 ), whereas passivated Si PV cells easily generate about 40 mA cm −2 (refs 5,6 ).…”
mentioning
confidence: 99%
“…Apart from these notable examples, most of the demonstrated solar-hydrogen devices place electrodes vertically in an electrolyte and do not investigate the limitations that bubble transport imposes on these systems. [54][55][56][57][58][59][60][61][62][63][64] In these cases, the devices rely on the upward movement of bubbles due to buoyant forces towards collection sites. In a deployable integrated solar-fuel generator, this configuration will pose significant challenges, as the photoabsorber will need to be placed normal to solar irradiation direction.…”
Section: à2mentioning
confidence: 99%
“…To mitigate these limitations, photoelectrodes can be designed in the microscale (e.g. microwires embedded into ion-conducting membranes 54,196,197 ) so that the lateral migration of ionic species is mainly dictated by distance between the reaction sites at opposite ends of the microstructures. The generalized discussion presented above summarizes some of the design principles for three prominent architectures of solarhydrogen generators.…”
Section: Coupled Processes In Integrated Solar-hydrogen Devicesmentioning
confidence: 99%
“…71 In the past decade, significant progress has been made in the exploration of new earth-abundant, inexpensive, and nontoxic catalysts for HER, including molybdenum sulfide, 116,117 firstrow transition metal dichalcogenides, 118,119 molybdenum carbide and boride, 120,121 tungsten carbide, 122 nickel phosphide (Ni2P), 123 cobalt phosphide (CoP), [124][125][126] , and nickel molybdenum (NiMo). 106,115,[127][128][129][130] The edge sites of molybdenum sulfide (MoSx) are analogous to the active center of the nitrogenase enzyme, while some surface cations of the first-row transition metal dichalcogenides resemble the ligand number and symmetry of active centers in hydrogenases (NiFe-hydrogenase, FeFe-hydrogenase, or Fehydrogenase). 116,131 The electronic structures of group VI transition metal carbides are similar to those of Pt-group metals.…”
mentioning
confidence: 99%